Digital Cultural Heritage Protection in the Era of Artificial Intelligence from the Perspective of Indonesian Intellectual Property Law - Dyah Permata Budi Asri; Intan Humaira (International Journal of Science and Environment (IJSE), 2026)
The development of artificial intelligence (AI) technology has presented both opportunities and challenges for intellectual property protection, particularly in the context of digital culture. Generative batik motifs, AI-based ethnic music, and folk tales reproduced through natural language processing are examples of new phenomena that raise legal questions regarding ownership, protection, and the rights of indigenous peoples. This study aims to analyze regulatory gaps in the protection of AI-based traditional cultural expressions (TCE’s) in Indonesia and offer alternative legal models. The research method used is normative juridical with a legislative, conceptual, and comparative approach, supplemented with empirical data in the form of preliminary interviews with cultural practitioners and law enforcement officials. The results of the study show that Indonesian IPR law still focuses on individual creators, is unable to address the issue of non-human creators, and is not accommodative of the communal nature of culture. A sui generis legal protection model is needed that is able to integrate the principles of cultural justice, benefit sharing mechanisms, and digital protection. This article offers ideas for a new regulatory framework that is expected to form the basis for the renewal of national intellectual property law.